Parenting of Migrant Worker Parents in Cultivating Early Childhood Independence - Yusuf, Ali; Lestari, Gunarti Dwi; Widodo, Widodo; Widyaswari, Monica; Wibowo, Adjie Pradana (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2025)
Independence is essential in early childhood as a foundation for managing one’s own life. Parents play a key role in developing this through their parenting approach. However, economic demands—especially in-migrant worker families—have reduced parental involvement as both parents often work outside the home. Therefore, this study aims to analyze the parenting of migrant worker parents in forming the independence of early childhood. The method employed in this study is a qualitative approach, utilizing a case study design. The data collection technique used is participatory observation and semi-structured interviews with parents and early childhood educators. The data analysis model applied is the Miles and Huberman model, which involves four stages: data collection, data reduction, data presentation, and data conclusion. The findings show that early childhood independence develops in stages among children aged 5 to 6 years. Some aspects—such as self-care and simple decision-making—have begun to emerge, while others, like emotional regulation and problem-solving, are still in the process of development. Under permissive parenting, children tend to show emerging social freedom but limited discipline. In contrast, authoritarian parenting fosters obedience but often restricts initiative and autonomy.